Martynapankowska123viz Martynapankowska123viz Matematyka Rozwiązane (a+b)-2a-6)-(a-26) = (3x-y+1)-(x+y)+ (y-x) = -(kx+my)-(3kx +2y) + (5 kordag (2ab +a+3)-(3ab-a+3)= (4x²-3x)-(x +0, 1x²)-(x²-0, ₁x) 6(x-4)-2= 2(x+1)-3(x-1)= 1-3(y-2) +4(y + 2) = ₁5(x-y-1)-4(x+2) = 7 2/(a+b)-2a-6)= (4x-4)-2x = x(x-1)-3(x²-x) = -20+46 SPEA -ab2a-x+5 x-y+1 kx-6ny +14 2a² 2x+13X-1 X-7 5a(a-3)-3a(a-5)= 3x-6 -5= 30-96-20-40= 2,9x²394a+46 - 2x²+2x a²+6²³ 2x+6 - 6x-9 = 4. * = 2² +9.x²1 = -b (x+7)(2x-1)= (2a-1)(a+4)= 5x-17 -x+6 6x-26 x-5y-13 (4a-1)(2-3a)= (a²-1)/(a +1)-8= TER (2k²-1)(2k+1)-4k²= (3p-p)(3-p)= (a-b)(a² + ab + b²) = (a+bXa²-ab+6²)= Edu Akcja!